1981
DOI: 10.1093/infdis/143.4.525
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Neisseria meningitidis to Human Mucosal Surfaces: Influence of Pili and Type of Receptor Cell

Abstract: The factors that determine attachment of meningococci predominantly to the mucosa of the nasopharynx rather than to other mucosal surfaces are unknown. Isolates of Neisseria meningitidis from the nasopharynx of carriers and from patients with meningococcal disease were found to be heavily piliated. Isogenic piliated and nonpiliated meningococcal clones were derived from blood and cerebrospinal fluid isolates. Meningococci with pili consistently attached to human nasopharyngeal cells in greater numbers than men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 34 publications
2
88
0
2
Order By: Relevance
“…On the other hand, neither the duration nor the severity of the underlying disease was significantly associated with an increased rate of adherence. The investigations focused on bacterial determinant of adherence indicated that serial sub-cultures lead to damage of the bacterial pili (De Voe and Gilchrist 1975) which are thought to be involved in attachment (Buchnan and Pearce 1976;Beachey 1981;Stephens and McGee 1981). In the present study, this possibility could be excluded, because the fresh isolates were stored in separate tubes of which one each was used for one experiment alone.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, neither the duration nor the severity of the underlying disease was significantly associated with an increased rate of adherence. The investigations focused on bacterial determinant of adherence indicated that serial sub-cultures lead to damage of the bacterial pili (De Voe and Gilchrist 1975) which are thought to be involved in attachment (Buchnan and Pearce 1976;Beachey 1981;Stephens and McGee 1981). In the present study, this possibility could be excluded, because the fresh isolates were stored in separate tubes of which one each was used for one experiment alone.…”
Section: Discussionmentioning
confidence: 83%
“…The basic method of in vitro adherence assay performed in this study is a modification of that of Stephens and McGee (1981) used in their recent work.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have subsequently reported that the association between pilus expression and virulence results from the ability of pili to facilitate adhesion of gonococci to the mucosal surfaces of the genital tract, the essential first stage in pathogenesis of gonococcal infection (reviewed by Heckels, 1989). Although the association of piliation with meningococcal disease is less well established, fresh meningococcal isolates from both blood and cerebrospinal fluid are invariably piliated, and pili facilitate adhesion of meningococci to nasopharyngeal cells in D i m , suggesting that they play an important role in colonization of the mucosal surfaces of the nasopharynx (Stephens & McGee, 1981;Trust et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…meningitidis is composed of various biologically active molecules, many of which are highly variable, most notably, OMP I1 (opacity 34-36 and pili (fimbriae).34,37*38 Pili are important adhesins in meningococci and isolates from patients are almost invariably pilate when observed microscopically. Pilation appears to be required for colonisation of host mucosal surfaces and for at least some stages of invasive disease caused by these bacteria.37, 39-43 Pili are filamentous protein appendages which extend considerable distances from the bacterial surface and are probably responsible for initial interaction with host epithelial cells and subsequently with endothelial cells.5, [42][43][44] Pili produced by pathogenic Neisseria spp. are composed of repeated subunits of pilin polypeptide with approximately 10 000 pilin subunits assembled to form an individual Meningococci have been observed to produce either one of two types of pilus, class I and class I1 (table II).576344346-52 Class I pili are The 53 N-terminal amino acids of mature pilin are conserved between antigenically distinct molecules constituting the conserved (C) region.…”
Section: Immunotype Ls-8 (B15 P1-4 Ls-8)mentioning
confidence: 99%